Prognostic value of perioperative NT-proBNP after corrective surgery for pediatric congenital heart defects - Fangqin Lin; Lingling Zheng; Yanqin Cui; Weidan Chen; Ramit Kumar Gupta; Huixian Li; Xinxin Chen; Huimin Xia; Huiying Liang (BMC, 2019)
Abstract Background It is critically important to assess the prognostic value of NT-proBNP in the form of repeated measures among children undergoing surgery for congenital heart defects (CHD). The aim of the present study is to assess the value of repeated perioperative NT-proBNP in evaluating the time dependent and temporal trajectory in prognostics diagnosis during the perioperative period in a large series of children with CHD. Methods Repeated measures of NT-proBNP from 329 consecutive children with CHD were obtained before and 1, 12, and 36 h after surgery, respectively. For fully utilizing longitudinal characteristics, we employed parallel cross-sectional logistic regression, a two stage mixed effect model and trajectories over time analysis to mine the predictive value of perioperative NT-proBNP on the binary outcome of prolonged intensive care unit (ICU) stay. Results The two stage mixed effects model confirmed that both the mean NT-proBNP level (aOR = 1.46, P = 0.001) and the time trends had prognostic value on the prediction of prolonged ICU stay. In the fully adjusted logistic regression analyses based on gaussian distributions, "rapidly rising NT-proBNP" put the subjects at 5.4-times higher risk of prolonged ICU stay compared with "slowly rising" group (aOR = 5.40, P = 0.003). Conclusions Comprehensive assessment of the time dependent and temporal trajectory in perioperative NT-proBNP, indicated by repeated measurements, can provide more accurate identification of children with higher risk of prolonged ICU stay after CHD surgery.